Salud mental en entornos penitenciarios - Lema, Aleida N. (2020)
The penitentiary system is the executing body of justice that guarantees compliance of the penalties of those who have broken the rule. The custodial sentence of freedom has as its purpose not only the prevention of the commission of new crimes and the security of society, but above all, the social rehabilitation of the offender. For it, the social rehabilitation system organizes a process made up of different resources, that are aimed at promoting the development of a series of cognitive skills, emotional, behavioral or occupational in an individual, in such a way that allow them to resume their life in freedom in a more adaptive and productive way. Within Of these strategies, mental health is a fundamental and indispensable element for this process is successful. This paper aims to describe the role of the mental health within the penitentiary context and, particularly, within the process of social rehabilitation.